Efficient correction of ABCA4 variants by CRISPR-Cas9 in hiPSCs derived from Stargardt disease patients - Laura Siles; Sheila Ruiz-Nogales; Arnau Navinés-Ferrer; Pilar Méndez-Vendrell; Esther Pomares (Elsevier, 2023)
Inherited retinal dystrophies comprise a broad group of genetic eye diseases without effective treatment. Among them, Stargardt disease is the second most prevalent pathology. This pathology triggers progressive retinal degeneration and vision loss in children and adults. In recent years, the evolution of several genome editing technologies, such as the CRISPR-Cas9 system, has revolutionized disease modeling and personalized medicine. Human induced pluripotent stem cells also provide a valuable tool for in vitro disease studies and therapeutic applications. Here, we show precise correction of two ABCA4 pathogenic variants in human induced pluripotent stem cells from two unrelated patients affected with Stargardt disease. Gene editing was achieved with no detectable off-target genomic alterations, demonstrating efficient ABCA4 gene correction without deleterious effects. These results will contribute to the development of emerging gene and cell therapies for inherited retinal dystrophies.